2012
DOI: 10.2131/jts.37.1071
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation stress induces hepatic hypertrophy in C57BL/6J mice

Abstract: -We previously reported that social isolation stimulated a stress response leading to increasing plasma corticosterone level and disruption of the hepatic lipid metabolism-related pathway, without changing body and organ weights, in mice after 4 weeks of social isolation stress, compared with the grouped-housing control (5 mice/cage). In this study, we evaluated the effects of social isolation stress for an extended period on physiologic changes in male C57BL/6J mice. Plasma corticosterone was reduced after 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
2
17
2
Order By: Relevance
“…Consumption of OID for 4 weeks, but not social isolation, increased the weight of epididymal visceral fat depot, consistent with an earlier study that did not find an increase in visceral fat depots by a short-term social isolation (Krolow et al 2013). However, a long-term social isolation is reported to increase visceral fat (Sakakibara et al 2012). Serum leptin levels were increased and adiponectin levels were reduced by long-term consumption of OID, consistent with the vast literature regarding the effects of obesity on these adipokines (Staiger et al 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consumption of OID for 4 weeks, but not social isolation, increased the weight of epididymal visceral fat depot, consistent with an earlier study that did not find an increase in visceral fat depots by a short-term social isolation (Krolow et al 2013). However, a long-term social isolation is reported to increase visceral fat (Sakakibara et al 2012). Serum leptin levels were increased and adiponectin levels were reduced by long-term consumption of OID, consistent with the vast literature regarding the effects of obesity on these adipokines (Staiger et al 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have reported no changes in leptin levels by social isolation in mice and rats (Krolow et al 2013, Volden et al 2013) and a reduction in adiponectin levels in mice (Sakakibara et al 2012). We conclude that changes in adipokines and higher amount of visceral fat likely explain insulin resistance in OID-fed mice, but not in socially isolated mice.…”
Section: Discussioncontrasting
confidence: 48%
“…Changes in the body weight of animals have been reported to be a convenient index for stress exposure [14,15]. A marked decrease in the body weight occurs in WIRS-and SDS-exposed animals [16]; in contrast, SIS promotes food intake and body weight gain [15,17]. These previous reports strongly support that in the present study, animals exposed to WIRS, SDS, or SIS were useful as stress models.…”
Section: Discussionsupporting
confidence: 86%
“…In mice, neither 2 nor 8 weeks of isolation changed body weight in adult mice despite altering feeding (Sun et al, 2014;Yamada et al, 2015). Only after 13 weeks of continuous social isolation has body weight and fat mass increased with increased feeding (Sakakibara et al, 2012). Many weeks of altered food intake appear to be required to modify body weight.…”
Section: Journal Of Young Investigatorsmentioning
confidence: 91%